Antibacterial Peptides from Tryptic Hydrolysate of Ricinus communis Seed Protein Fractionated Using Cation Exchange Chromatography - Tri Raharjo; Woro Utami; Atdrian Fajr; Winarto Haryadi; Respati Swasono (Universitas Gadjah Mada, 2021)
Antimicrobial peptide (AMP) peptide-based lead compound has become interesting target in developing new antibiotics. AMP is possibly generated through the digestion of protein. The protein of castor (Ricinus communis) seed is characterized as a ribosome-inactivating protein (RIP) that can be a source of AMP. The objectives of this research are to identify antibacterial peptides from Ricinus communis seed protein hydrolysate.   The seed protein was isolated using sodium dodecyl sulfate and subsequently digested using trypsin. The hydrolysate was fractionated using a strong cation exchange chromatography system, and the resulting fractions were tested for antibacterial activity. The peptides present in the active fraction were identified using high-resolution mass spectrometry. As the result, the pH 4 and pH 5 fractions of the elution buffer indicated antibacterial activity, with the pH 4 fraction of the hydrolysate having high activity against both gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus) bacteria. Three peptides that have the sequences EESETVGQR, GQSTGTGQQER, and LDALEPDNR could be responsible for the activity of the pH 4 fraction. The antibacterial activity of these peptides, which is due to their ionic properties and secondary structure, supports the disruption of the bacterial cell membrane. It can be concluded that Ricinus communis seed protein hydrolysate contains peptides with sequence EESETVGQR, GQSTGTGQQER, and LDALEPDNR that potent to be used as AMP lead compounds